Unraveling groundwater functioning and nitrate attenuation in evaporitic karst systems from southern Spain: an isotopic approach. - Valiente, Nicolás; Gil-Márquez, José Manuel; Gómez-Alday, Juan José; Andreo-Navarro, Bartolomé (Elsevier, 2020)
High evaporation rates in semi-arid to arid regions result in an increase in salinity that can exacerbate the effect of pollutants in water bodies.This study examines how groundwater drives pollution removal in wetlands, wells and springs within the Chaotic Subbetic Complexes (southern Spain). This evaporitic system, localy with a clear karstic functioning, is characterized by groundwater with a wide range of mineralization. Hydrochemical and multi-isotopic (δ34S, δ18O, δ15N, δ13C and δ2H) techniques were used to understand the geochemical processes leading to pollutant attenuation within the complexes. There, regional groundwater evolve from recharge/transition areas, with low salinity, to the discharge zone. Mineralization of groundwater depends on the dissolution of evaporitic deposits (gypsum, halite) of Keuper age, which increases salinity of the water drained by the outlet springs. δ15N and δ18O values of dissolved nitrate (NO3−) were used to estimate the relative contribution of N sources. NO3− is mainly derived from agricultural inputs (nitrate and urea fertilizers). Long-residence groundwater plays an important role in the biogeochemical evolution. Denitrification is responsible for NO3− removal in transitional zones and discharge springs. This process is promoted by the oxidation of organic carbon, derived from recharge areas and further transported to deeper zones of the aquifer. The findings of this study provide a new understanding of how hydrogeological functioning is connected to pollutant removal in an evaporitic karst system, where the scale of groundwater flows plays a key role in biogeochemical processes.
Keywords: Aguas subterráneas; Isótopos estables; Sal; Hidrología kárstica; Nitratos; Brine groundwater; Stable isotopes; Evaporitic karst groundwater; Solute transport; Nitrate attenuation